2008
DOI: 10.3201/eid1405.071347
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Aerial Spraying of Mosquito Adulticide in Reducing Incidence of West Nile Virus, California, 2005

Abstract: One-sentence summary for table of contents: Aerial spraying reduced incidence of human infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 22 publications
1
48
0
Order By: Relevance
“…However, one previous study that compared WNV disease incidence between treated and untreated areas during a substantial WNV disease outbreak in Sacramento County, California, showed that aerial mosquito adulticiding reduced human WNV disease cases. 12 Our findings support this conclusion and provide additional information because the California study evaluated the effect of spraying in areas where the primary WNV vectors are Culex pipiens and Culex tarsalis; our evaluation was conducted in counties where Culex quinquefasciatus is the main WNV vector. 8,13,14 Aerial spraying can treat large areas more rapidly than ground-based spraying, and using aircraft allows access to areas inaccessible by roads.…”
Section: Discussionsupporting
confidence: 77%
“…However, one previous study that compared WNV disease incidence between treated and untreated areas during a substantial WNV disease outbreak in Sacramento County, California, showed that aerial mosquito adulticiding reduced human WNV disease cases. 12 Our findings support this conclusion and provide additional information because the California study evaluated the effect of spraying in areas where the primary WNV vectors are Culex pipiens and Culex tarsalis; our evaluation was conducted in counties where Culex quinquefasciatus is the main WNV vector. 8,13,14 Aerial spraying can treat large areas more rapidly than ground-based spraying, and using aircraft allows access to areas inaccessible by roads.…”
Section: Discussionsupporting
confidence: 77%
“…The forecasting of RVF activity in these regions of Africa could have been used to potentially enhance various preparedness activities such as by targeting both adult and immature stages of the most important mosquito vector species. Costs of mosquito control are significant but have been shown to be effective in suppressing arbovirus transmission, 15 potentially reduce human and animal morbidity and mortality, and diminish economic impacts. Theoretically, the use of sustained release methoprene or other immature mosquito larval control products would be more costly than post outbreak control measures but massive applications at the earliest indications of elevated rainfall and before flooding would decrease the quantity of RVFV introduced into the environment by killing the majority of the mosquito reservoir before they are able to transmit the virus to domestic animals, thus diminishing the magnitude of the outbreak and potentially prevent more than $60 million in trade losses alone and losses in human and animal lives.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of evidence for the efÞcacy of vector control interventions to result in a decrease in human cases of Lyme disease is in stark contrast to other important vector-borne diseases, malaria perhaps being the best example, where epidemiological outcomes are routinely determined for control interventions that target the vector. There are also such examples emerging for West Nile virus disease in the United States, where an intervention focusing on the vector was followed up by determination of not only entomological but also epidemiological outcomes (Carney et al 2008).…”
Section: What Are the Epidemiological (Lyme Disease Reduction) Outcommentioning
confidence: 99%